VD_FINDINFO HC / 2011 / 130 vom 12. Januar 2011 - VD Tribunal cantonal (2011)
DIVORCE, OBLIGATION D'ENTRETIEN, RECOURS JOINT, INDEXATIONMONTANT, REVENU HYPOTHÉTIQUE | 125 CC, 128 CC, 159 al. 3 CC, 163 CC, 466 al. 1 CPC